Online preconcentration of lysozyme in hen egg white using responsive polymer coating in CE. Issue 18 (26th July 2021) - Wang, Yuchen; Li, Mengqin; Hu, Fei; Wang, Yanmei
Abstract: A mixed polymer brushes material based on poly (2‐methyl‐2‐oxazoline)‐ and poly (acrylic acid)‐coated capillary with switchable protein adsorption/desorption properties was applied for online preconcentration of lysozyme in hen egg white during capillary electrophoresis performance. First, lysozyme in simulated egg white was successfully online preconcentrated and the detection signal of lysozyme was amplified. Ovalbumin, ovomucoid, and conalbumin in egg white were verified show negligible interference on the online preconcentration of lysozyme according to the study on electroosmotic flow mobility. Second, a series validation procedure was carried out to evaluate the proposed method performance. There was a good linearity behavior range from 0.1 to 5.0 ng/mL, limit of detection was 20 pg/mL, and limit of quantity was 50 pg/mL, the accuracy and robustness of this method were also excellent. Last, the proposed method has been successfully used to detect and analyze lysozyme in hen egg white, the determined amounts of lysozyme in hen egg white were consistent with reported normal levels and recoveries were in the range of 96.0‐99.2%. After 75 consecutive runs, this prepared capillary was still stable for online preconcentration and determination of lysozyme in hen egg white without being affected by complex matrix.